2021
DOI: 10.21608/mvmj.2021.188544
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moringa olefiera on neurotoxicity induced by sodium fluoride in rats

Abstract: This study was carried out to evaluate the detoxifying effects of aqueous extract of Moringa Oleifera on sodium fluoride-induced neurotoxicity in male Wister rats. Design: Randomized controlled study. Animals: Forty rats Procedures: Rats were allocated into four equal groups (10 each). Basically, each group received the same basal diet for 30 days. The first group was not received additional treatment (negative control). However, the second group received 20 mg/kg b.wt sodium fluoride daily (positive control),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Anti-inflammatory and antioxidant potential of isolated plants have been demonstrated beneficial effects against neuritis, anxiety and spasm. 10,16 Many literature studies explored that the recurrence of oxidative stress, lipid peroxidation and mitochondrial dysfunction in CIS-evoked neurotoxicity. The administration of CIS causes cytotoxicity by generating ROS, lead to an elevation in MDA and fall in the activity of antioxidant defense enzymes like SOD, catalase, as well as a change in the concentrations of nonenzymatic components of GSH that prevent or protect against LPO in the brain tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-inflammatory and antioxidant potential of isolated plants have been demonstrated beneficial effects against neuritis, anxiety and spasm. 10,16 Many literature studies explored that the recurrence of oxidative stress, lipid peroxidation and mitochondrial dysfunction in CIS-evoked neurotoxicity. The administration of CIS causes cytotoxicity by generating ROS, lead to an elevation in MDA and fall in the activity of antioxidant defense enzymes like SOD, catalase, as well as a change in the concentrations of nonenzymatic components of GSH that prevent or protect against LPO in the brain tissues.…”
Section: Discussionmentioning
confidence: 99%
“…So, histopathological investigation revealed that inhibition of neurodegeneration in the MOLE treated rats compared with of the CIS treated rats. 16,22…”
Section: Discussionmentioning
confidence: 99%